Authoritarian attitudes and the perceived scientific legitimacy of anthroposophic medicine: A survey of attitudes on complementary and alternative medicine in Austria - Nikolas Reisecker; Julia Kuta; Levin Wieninger; Sebastian R. Leonard; Valentina Schmolik; Anita Rieder; Tanja Stamm; Edzard Ernst; Jutta Hübner; Harald H. Sitte; Valentin Ritschl (PLoS ONE, 2026)
Objectives This study investigates prevalence, usage, and perceived scientific legitimacy of anthroposophic medicine (AM) a prominent form of complementary and alternative medicine (CAM). It further explores associations with socioeconomic and psychological factors, with particular attention to authoritarian orientation, as measured by the KSA-3 scale and low ambiguity tolerance. Design/Setting A cross-sectional online survey was conducted among the Austrian population assessing sociodemographic characteristics, healthcare utilization, attitudes toward conventional medicine, AM, and CAM, as well as selected psychological variables. Participants A total of 429 individuals completed the survey. To enhance representativeness, the sample was post-stratified according to recent election results. Outcome Measures Regression models and appropriate statistical tests, selected based on data distribution and scale level, were used to evaluate associations between sociodemographic factors, psychological characteristics, and the use of and attitudes toward AM and CAM. Results Individuals over 50 showed higher CAM preference (p = 0.044), and were more likely to have used AM at least once (p = 0.083). Similarly, women showed higher CAM preferences (p = 0.004) and a higher likelihood of AM use (p < 0.001). Participants who viewed AM as scientific tended to be older (p < 0.001), have a higher income (p < 0.001), and resided more often in rural areas (p = 0.012). Psychologically, lower ambiguity tolerance and stronger perceived health control correlated with a stronger belief in AM’s scientific legitimacy (p < 0.05). Higher authoritarian orientation was also significantly associated with an increased belief in AM as scientific and a preference for eminence-based approaches (p < 0.001). Conclusions In our sample, we demonstrate how differences in specific socioeconomic and psychological factors correspond to differences in attitudes toward CAM and AM. These findings represent a promising foundation for more interdisciplinary research aimed at uncovering the underlying drivers of AM and CAM utilization.